Comparative analysis of climate change impact on livestock in relation to biomass base feed availability using standardized precipitation index in south-western Ethiopia - Amejo, A.G.; Gebere, Y.M.; Kassa, H.; Tana, T. (Academic Journals, 2018)
The standardized precipitation index and normalized difference vegetation index on event incidences (at different time scale) and biomass feed dry matter production, were used to assess climate change influences on feed availability. A significant decline (p<0.05) in feed dry matter availability indices across years was observed. The deviation from normality shows that the biomass feed production could vary significantly during drought occurrence years and this accelerates profoundly over time as drought frequency is expected to increase over time. The highest significant decline was observed in 2015 followed by 2006 and 2014. The results of analysis of the impact of climate change on livestock in relation to biomass dry matter production discretely subdivide different agro-ecological zones into land use land cover classes in southwestern Ethiopia. As represented by temporal scale drought, flooding and landslides were incidences considered as the major climatic risks in the study area. The risks threaten the livelihoods and even the security of the socio-ecological systems in general and such marginalized segments of the farming society in particular. The future needs effective action on environment management, devising adaptive and mitigation mechanism and change should aim at managing the occurrence and effects of extremes.